Kajian Risiko Penangulangan Tumpahan Minyak: Studi Kasus di Laut Jawa Bagian Barat - Andhi Setyonugroho; Ario Damar; I Wayan Nurjaya (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Risk of oil spill occured from oil exploration and production in marine should be effectively managed. This research is aim to obtain formula of oil spill risk analysis, risk mapping of oil spill in coastal area, and evaluated risk category in regard to be effectively risk management. The study area cover three coastal regions in western Java sea such as Kepulauan Seribu, Northern Java ( Banten, to Karawang coastline) and Eastern Lampung. Oil spill spreading modelling using Mike Zero from three spill sources (Cinta, Krisna and Widuri) resulted potentially impacted coastal by oil spill in certain - 8 months - period (January, February, March, April, May, June, July, and September). Study resulted the ALARP (As Low As Reasonable Practicable) matrix and risk category consist of  high, moderate, low and very low category which have range value  more  than  9.47, 9.46 – 4.23,4.22 – 3.75, less than 3.74, respectively. Mostly, 77% of the impacted coastal ecosystem and resource have moderate to high risk. Distribution of risks dominantly occurred in west moonson rather than east moonson. The matrix of division priority of oil spill mitigation based on cumulative risk exposure have high priority during west moonson occured in division 6, 7, 13 and 15 which were impacted to ecosystem of shoreline, mangrove, coral reef,  capture fishery, tourism, and sea port  area. Meanwhile, during the east moonson, division 2 and 4 have priority to impacted to shoreline,  mangrove ecosystem, marine culture, capture fishery and also tourism